(untitled) (ETIMA, 2021)
Аbstract In the successful functioning of modern society, the traditional educational methods are not enough, and new methods must be introduced. Given the constant development of technology today, a high-quality workforce is needed as much as possible. The fast changes in the modern way of living are forcing a life in virtual spaces, in which smart devices are an essential part. The e-learning concept offers several advantages to educational organizations that use this technology, including short and effective training, flexibility, and modulation. The Internet is increasingly used for a variety of online courses, so one of the essential tasks is understanding the e-learning security issues. The security aspect is very important for the companies creating e-learning platforms, which should consider the safety of the instructors, the students, as well as the companies / educational institutions that use the services. In this paper, we will look at the threats to the security and privacy of the most popular e-learning systems and suggest methods for overcoming those challenges. Keywords: e-learning, threats, security and privacy.